THE INVOLUTE-EVOLUTE OFFSETS OF RULED SURFACES - Kasap, E.; Yuce, S.; Kuruoglu, N. (SPRINGER INTERNATIONAL PUBLISHING AG, 2009)
In this study, a generalization of the theory of involute-evolute curves is presented for ruled surfaces based on line geometry. Using lines instead of points, two ruled surfaces which are offset in the sense of involute-evolute are defined. Moreover, the found results are clarified using computer-aided examples.
Keywords: Ruled Surface; involute-evolute; differential geometry; Science & Technology - Other Topics